Visual Disturbance in Multiple Sclerosis: The Effect of Tinted Spectacle Lenses - Sadeghi , Alireza; Moravej, Raheleh (Journal of Ophthalmic and Optometric Sciences, 2024)
This case report investigates the impact of tinted spectacle lenses on visual disturbances in a patient with multiple sclerosis (MS). A 42-year-old woman with preclinical-stage MS presented with severe photophobia and visual discomfort, despite normal visual acuity and the absence of ocular pathology. Conventional spectacles had failed to alleviate her symptoms. The patient reported marked improvement in visual comfort, reduced photophobia, and better tolerance to daily visual environments one month after being prescribed yellow-tinted lenses with medium density (category B). This case supports the potential utility of tinted lenses as a non-invasive, optical intervention for managing visual symptoms in MS. Further studies are warranted to assess the efficacy of various lens colors and densities across a broader spectrum of neurological disorders with visual complaints.